Analisis Pengaruh Pendidikan Kewirausahaan dan Pengetahuan Kewirausahaan terhadap Niat Berwirausaha yang Dimediasi oleh Pola Pikir Kewirausahaan - Ratnawati Ratnawati; Yudi Haliman; Sebastian Sebastian (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study aims to examine and analyze the influence of entrepreneurship education and entrepreneurial knowledge on students' entrepreneurial intentions in Indonesia which is mediated by an entrepreneurial mindset. The method in this study uses a quantitative approach by collecting data which is disseminated through the Google Form. The population in this study were Indonesian students who had received entrepreneurship education. The sampling technique used purposive sampling with a total of 109 respondents. The data analysis method used the partial least squares structural equation model (PLS-SEM) which was validated with SmartPls 3.0. The results of the study show that entrepreneurship education and entrepreneurial knowledge have an influence on students' entrepreneurial intentions in Indonesia. In addition, the entrepreneurial mindset also has a mediating role in the relationship between entrepreneurial knowledge and entrepreneurial intentions.